ELECTRONIC RECORD KEEPING TO SUPPORT INDONESIA E-GOVERNMENT IMPLEMENTATION - Anugrah, Esti Putri (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2020)
Background of the study: Electronic record keeping is one of the things that can significantly affect the implementation of e-government, because every transaction with the e-government will create electronic archives. However, many countries in the world still do not pay attention to the practice of managing their electronic archives, especially in developing countries, one of them is Indonesia. Purpose: This article aims to know the practice of electronic record keeping in the implementation of Indonesia e-government. Method: The writing method used in this article is a literature review by identifying secondary literary sources and archival legislation in Indonesia as a basis for conducting electronic record keeping. Findings: The implementation of electronic record keeping should be done well and correctly. Because when electronic record keeping in a government has been doing did good and true, it will automatically be able to support the implementation of e-government as already done by developed countries in the world.Conclusion: Electronic record keeping in developing countries is used as a strategy in implementing e-government.